The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism--R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
Keywords: HENRY, Richard; PALMER, Edward; TAWNEY, R.H.; THOMPSON, E.P.; capitalism; moral and ethical aspects; moral economy; socialism

Karl Polanyi: A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (1886–1964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. This biography shows how the major personal and historical events of his life transformed him from a bourgeois radical into a Christian socialist but also informed his ambivalent stance on social democracy, communism, the New Deal, and the shifting intellectual scene of postwar America.The book begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The narrative revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's connections to scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Karl Polanyi: A Life on the Left engages with Polanyi's biography as a reflection and condensation of extraordinary times. It highlights the historical ruptures, tensions, and upheavals that the thinker sought to capture and comprehend and, in telling his story, engages with the intellectual and political history of a turbulent epoch.
Keywords: European history; biography; history - Europe / Austria & Hungary; history - United States / 20th Century; history - modern; history - modern / 20th Century; social science; sociology

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

Commerce and Colonization in the Ancient Near East - Aubet, Maria Eugenia (Cambridge University Press, 2013)
In this analysis of the first colonialisms in history, the eastern roots of the Phoenician colonial system in the first millennium BC are traced and the metropolis of Tyre is established as the final link in a long chain of colonial experiences in the ancient Near East. The author reviews some of the theories and debates about trade and the colonial phenomenon, scrutinises the colonial situations that arose in the East in a context of long-distance interregional trade, and analyses the examples - Egypt, Byblos, Uruk, and Assur - where a metropolis with a mercantile tradition intervenes and acts as intermediary in different interregional exchange circuits. The success of a colonial metropolis is measured by its capacity to integrate dependent and complementary economies in circumstances where there is a strong demand for raw materials by the great powers. In that context, the profits obtained in the colonies thanks to price differentials between one region and another bring us back to the unending debate about the place of the economy in the ancient world and the pertinence of using features from modern economy - such as market, capital, private initiative, laws of supply and demand, and money - to explain the economies of the past.
Keywords: archaeology; business & economics; economic history; history / ancient / general

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Essais, Karl Polanyi, Sciences humaines - Seuil - Cangiani et al. (2008)
Essais, Karl Polanyi : L’ouvrage qui vaut à Polanyi une renommée mondiale ( La Grande Transformation paru en 1944) ne fut traduit en français qu’en 1983, signe (et cause aussi) d’une trop longue négligence pour un auteur désormais reconnu pour son apport incontestable aux sciences humaines et sociales ENG translation: The book which earned worldwide fame Polanyi (The Great Transformation, published in 1944) was not translated into French in 1983, a sign (and also because) of too long neglect for an author now recognized for his contribution Incontestable to the human and social sciences. Just back from the pendulum, this relative forgetfulness has given way to growing attention. This renewed interest is all the more justified because the thought of Polanyi is astonishingly topical. He is indeed the thinker par excellence of the "market society" and of the crisis to which a society is exposed where the logic of the market economy comes to dominate all spheres of human activity. Actually, Polanyi is still by his conception of a radically democratic socialism supposed to fulfill the modern ideal of freedom, by the weight it gives to culture and institutions in the analysis of economic systems, by its multidisciplinary method And by so many other traits which make it a reference today unavoidable in all the social sciences. These texts (mostly unpublished in French) offer a panorama of Polanyi's thought. There are of course keys to accessing the heart of the analysis grid proposed in The Great Transformation, but also a tool bringing together most of Polanyi's contributions to economic anthropology, the comparative study of systems Economics, political philosophy, and the analysis of systems and ideologies that clashed in the twentieth century (socialism, communism, fascism, Nazism).

Third Ways: How Bulgarian Greens, Swedish Housewives, and Beer-swilling Englishmen Created Family-centered Economies-- and why They Disappeared - Carlson, Allan C. (ISI Books, 2007)
Freewheeling capitalism or collectivist communism: when it came to political-economic systems, did the twentieth century present any other choice? Does our century? In Third Ways, social historian Allan Carlson tells the story of how different thinkers from Bulgaria to Great Britain created economic systems during the twentieth century that were by intent neither capitalist nor communist. Unlike fascists, these seekers were committed to democracy and pluralism. Unlike liberal capitalists, they refused to treat human labor and relationships as commodities like any other. And unlike communists, they strongly defended private property and the dignity of persons and families. Instead, the builders of these alternative economic systems wanted to protect and renew the “natural” communities of family, village, neighborhood, and parish. They treasured rural culture and family farming and defended traditional sex roles and vital home economies. Carlson's book takes a fresh look at distributism, the controversial economic project of Hilaire Belloc and G. K. Chesterton which focused on broad property ownership and small-scale production; recovers the forgotten thought of Alexander Chayanov, a Russian economist who put forth a theory of “the natural family economy”; discusses the remarkable “third way” policies of peasant-led governments in post–World War I Bulgaria, Poland, and Romania; recounts the dramatic and largely unknown effort by Swedish housewives to defend their homes against radical feminism; relates the iconoclastic ideas of economic historian Karl Polanyi, including his concepts of “the economy without markets” and “the great transformation”; and praises the efforts by European Christian Democrats to build a moral economy on the concept of homo religious—“religious man.” Finally, Carlson's work explains why these efforts—at times rich in hope and prospects—ultimately failed, often with tragic results. The tale inspires wistful regret over lost opportunities that, if seized, might have spared tens of millions of lives and forestalled or avoided the blights of fascism, Stalinism, socialism, and the advent of the servile state. And yet the book closes with hope, enunciating a set of principles that could be used today for invigorating a “family way” economy compatible with an authentic, healthy, and humane culture of enterprise.
Keywords: business & economics; economic history; economic theory; economics / comparative; history - modern; history / 20th Century

Globalization and Contestation: The New Great Counter-Movement - Munck, Head of Civic Engagement Dublin City University and Visiting Professor of Development Studies University of Liverpool and St Mary's University Nova Scotia Ronaldo; Munck, Ronaldo (Routledge, 2006)
Globalization is undoubtedly the great overarching paradigm of our era. However, there is still little agreement on what globalization actually ‘is’ and some do not accept that it ‘is’ anything at all. This new book addresses the contestation of globalization by the anti- or counter-globalization movement. To contest means to challenge, to call into question, to doubt, to oppose and to litigate. This study shows how globalization is ‘contestable’ in many different ways and how the counter-movements we have seen emerging over the last decade also ‘bear witness’ on behalf of an alternative human future. Ronaldo Munck presents an overarching framework that allows us to understand how globalization and its contestation are inextricably bound up with one another. This volume insightfully explores a number of case studies, including: the battle of Seattle in 1999 the World Social Forum peasant internationalism environmental movements and reactionary movements including: the US Patriot's movement, Islamic fundamentalist movements and other nationalist movements. Globalization and Contestation will be of great interest to all students and scholars of international relations, politics and of globalization and global governance in particular.
Keywords: countermovement; globalization; political economy; political science

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
Keywords: autobiography; biography; business & economics

Autour de Polanyi : vocabulaires, théories et modalités des échanges - Clancier, P.; Bresson, Alain (Editions De Boccard, 2005)
The varied questions which arise from the contributions made in this work provide a new modernity to Karl Polanyi and show the major interest in bringing together, as openly as his own, the various historical and economic specialties , Archaeological, ethnological, present in the House of Archeology and Ethnology of Nanterre. One of the most stimulating aspects of the contributions gathered here is the importance given to the presence of men, far beyond the simple equation of economic relations. These contributions sweep away a voluntarily vast field, from antiquity to the contemporary world. The historiographical dimension of Karl Polanyi's career is also present, through the contributions of Anne Chapman, who worked with him in South America, and his daughter, Kari Polanyi Levitt, specialist in development economics. Nathalie Zemon Davis, historian of societies in modern Europe, was asked to present the general conclusions of this symposium. Collection Conferences of Archaeology & Ethnology Maison René-Ginouvès , n o  1
Keywords: CHAPMAN, Anne; POLANYI LEVITT, Kari; ZEMON DAVIS, Nathalie

Ancient Athens & modern ideology: value, theory & evidence in historical sciences : Max Weber, Karl Polanyi & Moses Finley - Nafissi, Mohammad (Institute of Classical Studies, School of Advanced Study, University of London, 2005)
Keywords: Athens (Greece); WEBER, Max, 1864-1920; civilization; classical civilization; classical philology; economic theory; economics; history / ancient / Greece; social science / sociology / general

Chronik der grossen Transformation. Artikel und Aufsätze (1920-1945) / Wirtschaftliche Transformation, Gegenbewegung und der Kampf um die Demokratie - Cangiani, Michele; Thomasberger, Claus; Polanyi, Karl (Metropolis, 2002)
ENGLISH: In the last few years the interest in Karl Polanyi's work has been growing between 1920 and 1945, and with only a few exceptions they are difficult or impossible to access. The articles, essays, and manuscripts written in Vienna and England are not only the result of intensive studies during the central years of the author's life, but they are also the main part of his work. In this work, Polanyi analyzes a period decisive for the development of the twentieth century. The writings deal not only with the central problems and questions, the results of which are incorporated in his main work, The Great Transformation, published in 1944, without giving any further explicit insight, and thus provide an insight into the ideas, ideas, and reflections from which they emerged are. They are also (and above all) important time documents, significant as direct and immediate reflections on the political and economic events of the inter-war period. Polanyi analyzes with great care both the economic and political events, the global economic crisis as well as the international political situation, the attempts to create the conditions for peace and recovery, as well as the conflicts that point towards a new world war. The main topics for the Austrian economist include industrial restructuring, corporate tendencies, the rise of fascism and the transformation of the economic and political institutions in Great Britain and the USA during the New Deal period. These are supplemented by works on fundamental topics such as pricing, economic theory, sociology and the theory of socialism. All investigations are subject to a uniform, theoretically and politically fundamental question: How can - after the collapse of the liberal system of the 19th century such as the socialist hopes of the twenties - defend and expand democracy and freedom? The most important articles, essays and manuscripts, which were written in the period between 1920 and 1945, are grouped into three volumes according to their content. Volume I, entitled Economic Transformation, Counter-Movements and the Fight for Democracy, contains the analyzes on the areas of economy, global economic crisis and economic policy. The subject of Volume II is The international policy between the two world wars. Volume III, in which we have summarized the theoretical work on pricing, socialist economic analysis, Marxism, sociological theory, socialism, and democracy, is under the heading of freedom, democracy, and socialism. DEUTSCH: In den letzten Jahren wächst das Interesse an den Arbeiten, die Karl Polanyi zwischen 1920 und 1945 verfasste und die - mit wenigen Ausnahmen - bisher nur schwer oder gar nicht zugänglich sind. Die in Wien und in England geschriebenen Artikel, Aufsätze und Manuskripte sind nicht nur das Ergebnis intensiver Studien während der zentralen Jahre des Lebens des Autors, sie machen auch den Hauptteil seines Werkes aus. Polanyi analysiert in diesen Arbeiten eine für die Entwicklung des zwanzigsten Jahrhunderts entscheidende Periode. Die Schriften behandeln nicht nur die zentralen Problem- und Fragestellungen, deren Resultate, ohne erneut explizit aufgegriffen zu werden, in seinem 1944 publizierten Hauptwerk, The Great Transformation, einfließen, und geben damit Einblick in die Gedankengänge, Ideen und Überlegungen, aus denen jene hervorgegangen sind. Sie sind auch (und vor allen Dingen) wichtige Zeitdokumente, bedeutsam als direkte und unmittelbare Reflexionen über die politischen und wirtschaftlichen Ereignisse der Zwischenkriegsphase. Polanyi analysiert mit großer Sorgfalt sowohl die wirtschaftlichen wie auch die politischen Ereignisse, die Weltwirtschaftskrise wie die internationale politische Lage, die Versuche, die Bedingungen für Frieden und Aufschwung herzustellen, wie die Konflikte, die in Richtung eines neuen Weltkriegs weisen. Zu den Themen der hauptsächlich für den Österreichischen Volkswirt verfassten Artikel gehören die industrielle Restrukturierung, die korporativen Tendenzen, der Aufstieg des Faschismus sowie die Transformation der ökonomischen und politischen Institutionen in Großbritannien und in den USA während der Periode des New Deal. Diese werden ergänzt durch Arbeiten über grundsätzliche Themen wie Preisbildung, ökonomische Theorie, Soziologie und Theorie des Sozialismus. Allen Untersuchungen unterliegt eine einheitliche, theoretisch und politisch grundlegende Fragestellung: Wie können - nach dem Zusammenbruch des liberalen Systems des 19. Jahrhunderts wie der sozialistischen Hoffnungen der zwanziger Jahre - Demokratie und Freiheit verteidigt und ausgebaut werden?Die wichtigsten Artikel, Aufsätze und Manuskripte, die in der Periode zwischen 1920 und 1945 entstanden sind, werden nach inhaltlichen Schwerpunkten in drei Bände gruppiert. Band I, der die Überschrift Wirtschaftliche Transformation, Gegenbewegungen und der Kampf um die Demokratie trägt, enthält die Analysen zu den Themenbereichen Wirtschaft, Weltwirtschaftskrise und Wirtschaftspolitik. Gegenstand von Band II ist Die internationale Politik zwischen den beiden Weltkriegen. Band III, in dem wir die theoretischen Arbeiten zur den Fragen Preisbildung, sozialistische Wirtschaftsrechnung, Marxismus, soziologische Theorie, Sozialismus und Demokratie u.a. zusammengefasst haben, steht unter der Überschrift Freiheit, Demokratie und Sozialismus. InhaltMichele Cangiani und Claus ThomasbergerVorbemerkung9Marktgesellschaft und Demokratie: die Perspektive der menschlichen Freiheit. Karl Polanyis Arbeiten von 1920 bis 1945 11I.Politische Kämpfe in den zwanziger Jahren1.England und die Wahlen 462.Zur Krise der englischen Arbeiterbewegung513.Die neue Internationale564.Das Bergbauproblem in England635.Der englische Generalstreik726.Probleme des englischen Generalstreiks80II. Liberale Reformprojekte7.Liberale Wirtschaftsreformen in England908.Liberale Sozialreformer in England959.Schmalenbach und Liberalismus104III.Die Weltwirtschaftskrise10.Zur wirtschaftlichen Neuordnung Europas11011.Demokratie und Währung in England12012.MacDonald und die Wirtschaftspolitik12913.England auf der Waage13414.Kritik an Lausanne14215.Wirtschaft und Demokratie 14916.Weltinflationismus15517.Von Lausanne bis Washington16318.Brain-Trust siegt17019.Roosevelt zerschlägt die Konferenz178IV.Der Zusammenbruch der Demokratie in Deutschland und in Europa20.Gegenrevolution18621.Staatsgründung19322.Hitler und die Wirtschaft19923.Korporatives Österreich - eine funktionale Gesellschaft ?204V.Restrukturierung und Demokratie in England24.Wirtschaftsprogramm der Samuel-Liberalen21425.Ende der Slums21626.Englisches Stahlstatut21827.Technologische Arbeitslosigkeit22028.Elliot oder Empire ?22329.Probleme der Demokratie in England22630.Lohntarif-Bill in Lancashire22831.Lancashire im Fegefeuer23032.Lancashire als Menschheitsfrage23633.England überlegt24934.Labour und die Eisenindustrie25135.Gewerkschaftstagung in Weymouth25336.Labour in Southport25637.Tory-Planwirtschafter25938.Die Liberalen für Empirehandel261VI.New Deal39.Roosevelt im Verfassungskampf26440.Amerika im Schmelztiegel27141.Roosevelt im Kampf27942.T.V.A. - Ein amerikanisches Wirtschaftsexperiment28143.Arbeitsrecht in U.S.A.29044.Amerikanisches Gewerkschaftsgesetz verfassungsmäßig29145.Roosevelts strategischer Rückzug29346.Gewerkschaften in den U.S.A.295VII.Die Entwicklung in der Sowjetunion47.Zweiter Fünfjahresplan abgebremst29848.Wo hält Sowjetrußland?30849.Russischer Verfassungswandel316
Keywords: Polanyi essays

Naukratis: Trade in Archaic Greece - Möller, Astrid (Oxford University Press, 2000)
Archaic Naukratis was a busy trading place in the Western Delta of the Nile, renowned for its sanctuaries and courtesans, granting the Greeks access to Egyptian grain and luxury items. Now, more than one hundred years after the discovery and excavation of Naukratis, the author offers the first full-length analysis of the archaeology and archaic history of this important site. Although Naukratis always features in modern accounts of ancient Greek colonization, it was not a place where the Greeks could freely establish their own political and social organization--it was under the strict control of the Egyptian pharaoh and his officials. To understand the special status of Naukratis, the author takes the port of trade model, surveying the political, social, and economic background of both Late Period Egypt and archaic Greece. A major section of the book comprises an archaeological re-evaluation of the topography of archaic Naukratis and its material finds. The sanctuaries, archaic pottery styles, terracottas, faiences, statuettes, and other small finds are examined in the light of recent scholarship, and an in-depth study of the literary evidence is brought to bear on the archaeological material. This book comprises a significant contribution to our understanding of Graeco-Egyptian relations during the seventh and sixth centuries BC and also demonstrates that Polanyian economic theory can play an invaluable rï¿½le in the ongoing debate about the concepts best employed to analyse the ancient Greek economy.
Keywords: Ancient Egypt; business & economics; economic history; history